Finding Value in Nature. (1st August 2006) - Hill, Thomas
Abstract : This paper explores the idea that a proper valuing of natural environments is essential to (and not just a natural basis for) a broader human virtue that might be called 'appreciation of the good'. This kind of valuing can explain, without any commitment to a metaphysics of intrinsic values, how and why it is good to value certain natural phenomena for their own sakes. The objection that such an approach is excessively human-centred is considered and rebutted.